Renal Denervation for Treatment of Cardiac Arrhythmias: State of the Art and Future Directions. (27th October 2014) - KOSIUK, JEDRZEJ; HILBERT, SEBASTIAN; POKUSHALOV, EVGENY; HINDRICKS, GERHARD; STEINBERG, JONATHAN S.; BOLLMANN, ANDREAS
<x xml:space="preserve">Abstract</x> Renal Denervation for Treatment of Cardiac Arrhythmias. It has now been more than a quarter of a century since modulation of the sympathetic nervous system was proposed for the treatment of cardiac arrhythmias of different origins. But it has also been some time since some of the early surgical attempts have been abandoned. With the development of ablation techniques, however, new approaches and targets have been recently introduced that have revolutionized our way of thinking about sympathetic modulation. Renal nerve ablation technology is now being successfully used for the treatment of resistant hypertension, but the indication spectrum might broaden and new therapeutic options might arise in the near future. This review focuses on the possible impact of renal sympathetic system modulation on cardiac arrhythmias, the current evidence supporting this approach, and the ongoing trials of this method in electrophysiological laboratories. We will discuss the potential roles that sympathetic modulation may play in the future.